Identification of a Novel HIF-1α-αMβ2 Integrin-NET Axis in Fibrotic Interstitial Lung Disease - Khawaja, Akif A.; Chong, Deborah L. W.; Sahota, Jagdeep; Mikolasch, Theresia A.; Pericleous, Charis; Ripoll, Vera M.; Booth, Helen L.; Khan, Saif; Rodriguez-Justo, Manuel; Giles, Ian P.; Porter, Joanna C. (Frontiers in Immunology, 2020)
Neutrophilic inflammation correlates with mortality in fibrotic interstitial lung disease (ILD) however, the underlying mechanisms remain unclear. Neutrophil function is modulated by numerous factors, including integrin activation, inflammatory cytokines and hypoxia. Hypoxia has an important role in inflammation and may also contribute to pulmonary disease. We aimed to determine how neutrophil activation occurs in ILD and the relative importance of hypoxia. Using lung biopsies and bronchoalveolar lavage (BAL) fluid from ILD patients we investigated the extent of hypoxia and neutrophil activation in ILD lungs. Then we used ex vivo neutrophils isolated from healthy volunteers and BAL from patients with ILD and non-ILD controls to further investigate aberrant neutrophil activation in hypoxia and ILD. We demonstrate for the first time using intracellular staining, HIF-1α in neutrophils and endothelial cells in ILD lung biopsies. Hypoxia enhanced both spontaneous and phorbol 12-myristate 13-acetate (PMA)-induced neutrophil extracellular trap (NET) release (NETosis), neutrophil adhesion, and trans-endothelial migration. Hypoxia also increased neutrophil expression of the αM and αX integrin subunits. Interestingly, NETosis was induced by αMβ2 integrin activation and prevented by cation chelation. Finally, NETs were demonstrated in the BAL from ILD patients, and quantification showed increased cell-free DNA content and MPO-citrullinated histone H3 complexes in ILD patients compared to non-ILD controls. In conclusion, HIF-1α upregulation may augment neutrophil recruitment and activation within the lung interstitium through activation of β2 integrins. Our results identify a novel HIF-1α-Integrin-NETosis axis for future exploration in therapeutic approaches to fibrotic ILD.